Development of a Games Book Media to Improve Early Reading Skills of Second-Grade Elementary School Students - Wahyuni, Hilda; Susilawati, Samsul; Yaqin, Mohamad Zubad Nurul (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2025)
Reading ability is fundamental for literacy development, yet many Indonesian students, including those at MIS Al-Hidayah Karangploso, struggle with simple texts due to limited engaging learning media. This study developed and evaluated an interactive Games Book to enhance early reading skills among 32 second-grade students using the ADDIE-based R&D approach. The digital flipbook integrates progressive reading stages (words, sentences, texts) with game-based activities providing immediate feedback and sustained engagement. Expert validation indicated high content validity with I-CVI = 1.00 for media, material, and language. Media was visually appealing and technically reliable; material was relevant, accurate, and engaging; language was appropriate, readable, and clear. Teacher and student responses confirmed strong practicality. Effectiveness testing showed students’ average scores increased from 63.78 to 91.56 (N-Gain = 0.8, high category), with Paired Sample t-test Sig. = 0.000 < 0.05. Furthermore, Cohen’s d = 1.51 and the 95% confidence interval (–34.90 to –20.66) indicate that the improvement was both statistically significant and practically meaningful. The Games Book is therefore highly valid, practical, and effective in improving early reading skills and motivation through structured, interactive digital learning experiences.